2017
DOI: 10.18632/oncotarget.22201
|View full text |Cite
|
Sign up to set email alerts
|

ABCB13435TT andABCG2421CC genotypes were significantly associated with longer progression-free survival in Chinese breast cancer patients

Abstract: ObjectiveTo investigate the distribution of ABCB1 C3435T and ABCG2 C421A gene polymorphisms in Chinese Han population and their influences on the susceptibility and prognosis of breast carcinoma.MethodsA total of 200 female subjects were enrolled in this study, comprising 100 breast cancer patients and 100 healthy controls. Carcinoma and para-carcinoma tissues were collected from the breast cancer patients, while peripheral blood was collected from healthy controls. Single nucleotide polymorphisms (SNPs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The association between ABCB1 polymorphisms and the prognosis of patients following taxane-containing chemotherapy has been explored in several studies. However, the findings are inconclusive, with contrasting results and weak data (Grau et al, 2009;Bergmann et al, 2011;Qiao et al, 2016;Li et al, 2017;Priyadarshini et al, 2019;Zhong et al, 2019). Given the potential importance of ABCB1 polymorphisms in the response to chemotherapy, we conducted a meta-analysis of studies conducted to date, along with data obtained by doctors, pharmacists, and statisticians, to systematically integrate the current pharmacogenetic literature and obtain more credible evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The association between ABCB1 polymorphisms and the prognosis of patients following taxane-containing chemotherapy has been explored in several studies. However, the findings are inconclusive, with contrasting results and weak data (Grau et al, 2009;Bergmann et al, 2011;Qiao et al, 2016;Li et al, 2017;Priyadarshini et al, 2019;Zhong et al, 2019). Given the potential importance of ABCB1 polymorphisms in the response to chemotherapy, we conducted a meta-analysis of studies conducted to date, along with data obtained by doctors, pharmacists, and statisticians, to systematically integrate the current pharmacogenetic literature and obtain more credible evidence.…”
Section: Introductionmentioning
confidence: 99%
“…There are differences in the genetic and biological characteristics, clinical progression pattern, therapeutic responses, and prognoses among different tumor types; the distribution of paclitaxel in different tumors is also different [38]. Sensitivity analysis revealed that the study by Li et al [21] was a source of statistical heterogeneity. When this outlier study was removed, there was no evidence of heterogeneity in the four remaining studies in the C3435T homozygote model.…”
Section: Discussionmentioning
confidence: 99%
“…Significant heterogeneities were found in the overall meta-analysis of the homozygote model (I 2 = 53%, P = 0.04) and dominant model (I 2 = 76%, P = 0.04). Sensitivity analyses showed that heterogeneity was decreased in the heterozygous model (I 2 = 12%, P = 0.34) after excluding the study by Li et al [21].…”
Section: Pfsmentioning
confidence: 93%
See 1 more Smart Citation
“…In Kurdish BC patients, the A allele of the rs2231142 SNP may be a risk factor for BC progression, while the C allele was associated with poorer responses to anthracyclines and paclitaxel [22]. In contrast, the homozygous (CC) genotype of the ABCG2 SNP rs2231142 was significantly associated with longer progression-free survival in Han Chinese BC patients [23]. In the present study, the ABCG2 SNP rs2231142 was found to be significantly associated with axillary lymph node status in Jordanian BC patients.…”
Section: Discussionmentioning
confidence: 99%